Hyaluronic acid coated albumin nanoparticles for targeted peptide delivery in the treatment of retinal ischaemia. (June 2018) - Huang, Di; Chen, Ying-Shan; Green, Colin R.; Rupenthal, Ilva D.
Abstract: Recent studies have shown that Connexin43 mimetic peptide (Cx43 MP) can prevent secondary damage following retinal ischaemic and inflammatory disorders by blocking uncontrolled Cx43 hemichannel opening. However, limitations in peptide stability and the presence of various intraocular barriers limit efficient retinal delivery in the clinical setting. The present study aimed to achieve targeted and sustained peptide delivery to the retina by encapsulating Cx43 MP into hyaluronic acid (HA) coated albumin nanoparticles (NPs). Intraocular biodistribution, particle retention, retinal targeting, and therapeutic efficacy of intravitreally injected NPs encapsulating Cx43 MP were evaluated in a rat model of retinal ischaemia-reperfusion injury. NPs rapidly diffused through the vitreous and specifically targeted CD44-expressing retinal cells. NPs remained at the target site for extended periods enabling sustained peptide release and thus prolonged therapeutic action. Compared to free Cx43 MP, Cx43 MP loaded NPs enabled enhanced therapeutic efficacy preventing thinning of retinal layers and disruption of retinal blood vessels. Immunohistochemical results confirm that Cx43 MP loaded NPs efficiently reduced Cx43 expression, thereby suppressing ongoing inflammation and preventing the loss of retinal ganglion cells. Overall, HA coated NPs could have great potential as a peptide delivery platform in the treatment of chronic retinal degenerative and inflammatory disorders. Graphical abstract: